Achieving organizational agility, intelligence, and resilience through information systems - Rahman, Hakikur, 1957- (Advances in business information systems and analytics (ABISA) book series., 2022)
"This book presents the latest scholarly research on the widespread integration of technological innovations around the globe and examines how organizational agility, intelligence and resilience interprets, affects, and improves the entrepreneurship around the globe"--